2019
DOI: 10.1177/0267658319877666
|View full text |Cite
|
Sign up to set email alerts
|

Language proficiency is only part of the story: Lexical access in heritage and non-heritage bilinguals

Abstract: This study examined how language proficiency and age of acquisition affect a bilingual language user’s reliance on the dominant language during lexical access. Two bilingual groups performed a translation recognition task: Mandarin–English classroom bilinguals who acquired their dominant language (Mandarin) from birth and their non-dominant language (English) post-puberty through formal classroom instruction, and Mandarin–English heritage bilinguals who acquired their non-dominant language (Mandarin) at home f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…On a par with previous findings (Brysbaert et al 2016;Monaghan et al 2017), the results of the current study confirm that language exposure plays a key role in the process of lexical access in that more exposure to home Kurdish media and more exposure to Kurdish in kindergarten and school lead to richer lexical-semantic associations, which is necessary for accelerating the processing speed. Furthermore, as Wiener and Tokowicz (2021) speculate, exposure to a language frequently over a long period of time in a naturalistic setting strengthens conceptual links that might not require a reference to lexical form information in the lexical access process.…”
Section: Effects Of the Individual Input Quantity And Quality Factors...mentioning
confidence: 74%
“…On a par with previous findings (Brysbaert et al 2016;Monaghan et al 2017), the results of the current study confirm that language exposure plays a key role in the process of lexical access in that more exposure to home Kurdish media and more exposure to Kurdish in kindergarten and school lead to richer lexical-semantic associations, which is necessary for accelerating the processing speed. Furthermore, as Wiener and Tokowicz (2021) speculate, exposure to a language frequently over a long period of time in a naturalistic setting strengthens conceptual links that might not require a reference to lexical form information in the lexical access process.…”
Section: Effects Of the Individual Input Quantity And Quality Factors...mentioning
confidence: 74%
“…We decided to investigate the extent to which exposure to English could affect adjectival ordering in the Spanish of heritage speakers. As it has been shown in the past, heritage speakers show differential access to representations in productive and receptive tasks (Perez Cortés et al 2019, Putnam & Sánchez 2013 and their results in those tasks may also be affected by their level of proficiency (Wiener & Tokowicz 2019). In order to cover both productive and receptive data as well as a measure of proficiency, the study included four parts: a linguistic background questionnaire, a proficiency task, an acceptability judgment task, and an interpretive task presented using Qualtrics software (Qualtrics, Provo, UT).…”
Section: The Studymentioning
confidence: 90%
“…Previous research has established a connection between lexical access and heritage speakers' proficiency in their heritage language (Montrul and Foote 2014;Wiener and Tokowicz 2021). Building on previous works, we measure lexical access by means of the Multilingual Naming Test (MiNT) (Gollan et al 2012), which has been shown to correlate well with both self-reported and objective measures of language proficiency.…”
Section: Lexical Accessmentioning
confidence: 97%
“…These low access levels have been found to correlate with innovative forms (Giancaspro 2019;Hur 2020), particularly in nominal and verb inflection (Hur et al 2020;López-Otero 2022;Goldin et al 2023). Beyond inflection, Montrul's (2014) and Hur's (2020) work on differential object marking have opened the path to examining the effect of linguistic factors such as lexical access (Bialystok et al 2008a(Bialystok et al , 2008bGollan et al 2011Gollan et al , 2012, language dominance (Birdsong 2014;Gertken et al 2014;Amengual 2023), and patterns of language use (Bedore et al 2012;De Carli et al 2015;Giancaspro 2019;Kastenbaum et al 2019) on other aspects of the heritage language (Flores et al 2017;Giancaspro 2019;Montrul et al 2008;Montrul and Foote 2014;Dubiel and Guilfoyle 2021;Wiener and Tokowicz 2021). The expression of telicity in Spanish as conveyed by verbs with the clitic se in sentences such as (1) is one of such aspects:…”
Section: Introductionmentioning
confidence: 99%